Strategy Analysis To Improve The Competitiveness Of Tourist Villages Using The Analytical Hierarchy Process (AHP) Approach - Susilo, Joko Hadi; Astuti, Hartiningsih; Atmaja, Dimas Surya; Fatmawati, Dewi; Alfiyana, Siti (Trunojoyo University of Madura, 2024)
This study was conducted with the aim of determining the strategies that must be carried out in increasing the competitiveness of tourist villages through several strategies proposed based on the calculation of priority weights including increasing human capital, increasing knowledge of environmental sustainability, increasing the quality of organizational culture, capital management and participatory planning. This research method was carried out using a hierarchy process analysis approach to determine priority strategies from predetermined multicriteria, the data in this study were questionnaires given to key persons based on the level of knowledge about the competitiveness of tourist villages. The findings of this study can be explained that in an effort to increase the competitiveness of tourist villages, it is necessary to consider priority aspects in an effort to improve the strategy for more optimal tourist villages. This study found that the main priority in increasing the competitiveness of tourist villages can be done through a strategy of increasing human capital through training, education and improving skills. In the strategy of increasing the competitiveness of tourist villages, strategic steps in priority levels must be sorted according to the main priorities starting from increasing human capital, participatory planning, increasing the quality of culture and organizations as well as environmental sustainability and capital management. Collaboration between business actors, local governments and stakeholders is known to be very important in implementing the concept of sustainability to achieve highly competitive tourist villages.